A Gramscian Perspective on Colonial Baroque: Goa 1650s-1720s - Gusella, Francesco (Eikón / Imago, 2021)
The present study provides a comparative analysis of whitewashed stucco moldings and polychrome gilded altarpieces, major elements of the distinct decorative style that originated in colonial Goa during the period under investigation. The study’s comparative approach focuses on the combination of these materials and the entangled evolution of their decorative motifs. The article employs Antonio Gramsci’s theory of cultural hegemony to analyze the artistic patronage of a selected group of religious buildings that are particularly important from the perspective of their decorative program. The theory of cultural hegemony is applied to the discursive and stylistic formulations of the local secular clergy against the background of jurisdictional conflict between the Crown and the Holy See. Through this approach, this study highlights the ability of local elites to legitimize their status and assert their dominance though active consensus strategies, namely the persuasive effects of baroque architecture. The distinct quality of the Goan baroque that emerged within this process of artistic appropriation, is here interpreted in its transversal, emulative and intrinsically allusive aspects.